Where are we going? Where have we been?: The climate for diversity within urban planning educational programs - Greenlee, AJ; Jackson, A; Garcia-Zambrana, I; Lee, CA; Chrisinger, B (SAGE Publications, 2018)
This paper summarizes findings from a nationwide survey of degree-seeking urban planning students regarding the climate for diversity within their degree programs. This study examines interactions within the classroom, with faculty, with peers, and with professional planners. From May to October 2016, we surveyed 451 students and conducted in-depth interviews with 25 students. Our results show that while the majority of students report a positive climate for diversity within their programs, many still report occurrences of bias and discrimination, describe the shortcomings of a lack of planning faculty diversity, and perceive persistent challenges around diversity within planning practice.